Corona Virus Saga: How Happy were the People of Niger State from the slant of income? (Lapai Journal of Economics, 2024)
The dramatic and widespread impacts of the COVID-19 pandemic made government responses serious and the major line of actions globally is the ‘lockdown policy actions’ premeditated to cushion the effect of spread. Apart from the known negative effects of pandemics on lives and properties, the global policy responses of lockdown is accompanied with mental challenges that includes boredom, loneliness, depression, suicide, etc. that affects people’s happiness negatively. The objective of this work is to ascertain effect of corona virus on the happiness of the people of Niger State using income as an approach. This was motivated largely by the novelty of such study in the study area and the method employed at processing the data is factor analysis model. The findings revealed that most of the constructs show magnitudes of moderate and low correlations meaning that the level of people’s impacting responses of Covid-19 to happiness is not high. The result therefore, suggests that although, people’s responses to Covid-19 lowered their happiness in Niger State but the impact is moderate.